Prasse, Karl-G. 2010. Tuareg Elementary Course - Souag, Lameen (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
The dialect discussed in this book, Tahaggart, is numerically insignificant in comparison, spoken in Algeria and Libya around the Ahaggar Mountains by hardly more than 50,000 people; however, it is of particular historical and anthropological interest for its relative isolation both from Arabic and from sub-Saharan African languages, and was the subject of some of the earliest comprehensive lexicography (Foucauld 1951). The author of the book under review, Karl-G. Prasse, has devoted much of his long career to the linguistic study of Tuareg, including his four-volume Manuel de grammaire touaregue (tahǎggart) (Prasse 1972). In this book he returns to the theme of Tuareg grammar, bringing to it the benefit of his intervening years’ experience.